Improving Students Vocabulary Using Flashcards - Hana Fitriana Khoerunnisa; Dina Windiarti; Alfaira Nazwa; Asadelya Adora Rahma Putri; Eka Nurhidayat (Papanda Journal of English Education, 2024)
The objective of this study is to ascertain the impact of using flashcards as a medium to enhance the English vocabulary of junior high school students. The research method employed is a quantitative approach, incorporating a quasi-experimental design. The subjects of the research study were divided into two classes: an experimental class that received a treatment consisting of learning using flashcards, and a control class that did not receive the treatment and continued to learn using conventional methods. The instrument employed was a single-test, which was utilized to assess students' vocabulary skills following the culmination of the learning process. The findings of the data analysis demonstrated a substantial discrepancy in the vocabulary scores of students in the experimental and control classes. The utilization of flashcards as a learning aid has been demonstrated to yield higher test scores in comparison to learning without the use of media. This finding indicates that the utilization of flashcards is an effective strategy for enhancing junior high school students' English vocabulary acquisition. Consequently, flashcards emerge as a viable alternative learning strategy, characterized by its engaging, interactive nature, and ease of implementation in the context of English language instruction in schools.